Evaluation of the Performance of Clay-Based Bricks With the Addition of Co-combustion Ash (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
The gradual replacement of coal by local renewable resources leads to an increased production of co-combustion ashes (CC). Their disposal can be limited by their use in the construction sector, where they can partially replace primary raw materials. This study evaluates the incorporation of selected Slovenian CC ash into clay-based fired bricks within the EU AshCycle project. The tests included the measurement of water absorption, porosity, density, weight loss, shrinkage, flexural and compressive strength, and freeze-thaw resistance. Two types of clay were used to compare the influence of the selected ash on the performance of the fired samples. Replacing clay mixtures with 10 wt% CC ash reduced the compressive strength of the fired bricks but it still reached the required 10 MPa as specified in EN 772-1 (2015). The addition of CC ash to fired bricks requires careful planning of the raw mixes, taking into account various parameters that may affect the properties of the products.